Space Syntax Analysis on Edu-Tourism Accessibility (Case Study: Planetarium UIN Walisongo Area) - Alifiano Rezka Adi; Selamet Riyadi (Sinektika: Jurnal Arsitektur, 2023)
Planetarium UIN Walisongo is an educational facility that not only accommodates academic needs but is also projected to become a tourism destination in Semarang. The density of activity is the main focus that must be considered. The building's existence in the middle of the campus also demands that it has good visual access. The study focused on configuration and visibility analysis by looking at their effect on accessibility around the building. The research was conducted using quantitative methods with a descriptive and simulation framework. The simulation process is carried out using a space syntax approach with Depthmap software. Macroanalysis shows that the building is located in the central area with a relatively high integration value. The high intelligence value shows that the spatial configuration is relatively easy to recognize. The wide and integrated road makes this area have relatively high visibility. Microanalysis shows that the pedestrian around the Planetarium is not well connected. Space engineering by connecting pedestrians is carried out to provide better accessibility. Achievement efficiency is the main consideration to produce a high value of integration and visibility around the building. Therefore, the area quality will be better with an accessible space on macro and micro scales